ESTIMATION SURFACE RUNOFF CHARACTERISTICS OF HISHKARO BASIN, DUHOK GOVERNORATE USING SOME HYDROLOGICAL APPROACHES - MOHAMMED, RAMADHAN HAMZA (Journal of Duhok University, 2021)
An analysis of some hydrological characteristics specifically surface runoff of Hishkaro stream basin located in Duhok Governorate-Kurdistan Iraq was conducted. The available historical recorded rainfall data in Duhok and Zawita meteorological stations were used to calculate maximum daily rainfall using probability distribution for number of return periods. Natural resources conservation service method (NRCS) is used to estimate daily surface runoff at the outlet of the basin. Then runoff coefficient, monthly and annual surface runoff volume were predicted.  A maximum daily surface runoff for different probability distribution and number of return period was calculated too which is an essential parameter in the design process of any future required hydraulic structures on Hishkaro stream